Development of Three˗Tier Diagnostic Test Instrument to Measure Misconceptions of Class XI Students on Reaction Rate Materials - Natalia, Putri Dewi; Sudrajat, Ajat (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
This study aims to measure and detect student misconceptions that occur in the concept of reaction rate based on the diagnosis results of Grade XI Negeri 2 Kabanjahe students and to show subconceptions that experienced both high and low misconceptions. The study was conducted in March–April 2022. The type of research used is Research and Development with ADDIE development. Methods used are tests, anchors, interviews and documentation. The diagnostic test developed is a threetitier multiple choice diagnostic test consisting of an answer choice, reason and confidence level. Validation result by validator indicates the developed instrument is valid. The validity of the developed test is 20 valid problems and 10 invalid problems. Reliability test results show a reliability figure of 0.85. The highest percentage of misconceptions in collision theory is 51.5% and the lowest percentage of misconceptions in reaction order and reaction rate equations is 26.72%. The percentage of students who understand the concept of reaction rate is 35%. The percentage of categories did not understand the concept of reaction rate by 27% and the percentage of misconceptions of reaction rate by 38%.